Reflexivity and Dialogue in Collaborative Ethnography: the Ethnographic Accompaniment of a Mexican “Intercultural” Educational Institution - Dietz, Gunther (Revista de Antropología Social, 2012)
Starting from an ethnographic-dialogical case study on the Universidad Veracruzana Intercultural (UVI) in Mexico, in which I pretend to combine principles of “activist anthropology” with a “doubly reflexive ethnography”, this paper analyzes how in the process of interculturalizing educational institutions new methodological options arise and how these may contribute to nurture, refresh and decolonize classical anthropological ethnography. Strongly influenced by discourses and models of intercultural education, the so called “intercultural higher education” in Mexico is emerging as a new university sub-system, aimed at providing a culturally pertinent university training to ethically, linguistically and/or culturally diverse students. The ethnographic analysis starts with the official intercultural discourse and contrasts it with the praxis of educational diversity management, as offered in a non-conventional B.A. program. From the “glocal” dialogue between different academic and peasant, external and internal ways of knowledge we develop a series of proposals to modify the curriculum of this B.A. program. Accordingly, a “dialogue of knowledge”, which implies “inter-cultural”, “inter-lingual” and “inter-actor” dimensions, obliges academic anthropology to revise its methodological practice. This paper therefore concludes with a proposal to redefine ethnographic practice in terms of dialogues and shared reflexivity among diverse actors.
Keywords: reflexive ethnography; dialogue of knowledge; intercultural higher education; Veracruz; Mexico